Improved switching‐table‐based DTC strategy for the post‐fault three‐level NPC inverter‐fed induction motor drives. Issue 1 (29th September 2017) - Tang, Qidi; Ge, Xinglai; Liu, Yong‐Chao; Hou, Maojun
Abstract : In this study, a direct torque control (DTC) strategy based on a novel switching table for induction motor drives fed by the eight‐switch three‐phase inverter (ESTPI), which is the post‐fault reconfigured topology for the three‐level neutral‐point‐clamped inverter with the open‐circuit fault occurring in a leg, is proposed to reduce the torque ripple and suppress the dc‐link capacitor voltages offset. The influence of each basic voltage vector provided by the ESTPI on the stator flux, the electromagnetic torque and the dc‐link capacitor voltages is analysed in detail, and the causes of the torque ripple and the capacitor voltages offset are also revealed. To suppress the dc‐link capacitor voltages offset, a hysteresis comparator is added to regulate the dc‐link capacitor voltages. Based on that, an optimised switching table to achieve not only torque ripple reduction but also dc‐link capacitor voltages offset suppression is proposed. The feasibility and the effectiveness of the proposed DTC strategy are verified by simulations and experimental results.